Stockman's veterinary handbook - Nelson, Roger, ed. (Livestock Development Company GeorgetownGY, 1986)
Discusses general principles of the causes, control and prevention of animal diseases. Outlines the steps to be followed in the performance of post-mortem examinations of cattle, the collection, preparation and preservation of samples from living or dead animals. Discusses the administration and use of medicines in cattle. Examines the causes, effects, control, and prevention of several cattle and horse diseases in Guyana, at times describing the life cycle of the parasite causing the disease. Provides techniques to help stockman in pregnancy testing, delivery, castration, branding and recognition of age of cattle.